(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
Abduction, often defined as inference to the best explanation, is a type of reasoning that is employed in situations where there is some kind of puzzling evidence, which is to be explained by the best hypothesis available. Amongst the different fields of application of abductive reasoning, the medical field plays an especially important role, primarily in its diagnostic aspect, where an accurate diagnosis of the cause of a patient’s condition is to be established. In this paper, an attempt is made to elaborate on the logical and epistemological aspects of the diagnostic application of abductive reasoning. The work of a fictitious medical diagnostic genius, David Shore’s Doctor House, is used as an illustrative example of the complexity and the challenging nature of this kind of reasoning. The main purpose of the analysis presented in the paper is to test the plausibility of the dominant theoretical explanations of abductive reasoning, especially in regard to its structure, dynamics and practical usability in the medical field, and to identify its elements that deserve a more comprehensive theoretical treatment from an epistemological point of view.